EFFECT OF MERCURIC SULPHATE AND CADMIUM SULPHATE ON THE OXYGEN CONSUMPTION AND RATE OF OXYGEN CONSUMPTION IN ESTUARINE CRAB SCYLLA SERRATA (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2025)
Physiological responses oxygen consumption of estuarine crab Scylla serrata were exposed to the sub-lethal concentration of cadmium sulphate and mercuric sulphate for the present investigation up to 24, 48, 72, 96, 120 hrs (17.2mg/L, 6 mg/L), respectively. The oxygen consumption was initially slight increased (24 hrs) and then decreased throughout the experiment in both the treated groups as compared with control group.